Epidemiology of Acromioclavicular Joint Sprains in 25 National Collegiate Athletic Association Sports: 2009-2010 to 2014-2015 Academic Years. (October 2016) - Hibberd, Elizabeth E.; Kerr, Zachary Y.; Roos, Karen G.; Djoko, Aristarque; Dompier, Thomas P.
Background: No previous studies have described the incidence of acromioclavicular (AC) joint injuries in a large sample of National Collegiate Athletic Association (NCAA) student-athletes. Such data are needed to understand the injury prevalence, mechanisms of injury, and recovery patterns in NCAA student-athletes. Purpose: To describe the epidemiology of AC joint sprain injuries in 25 NCAA championship sports. Study Design: Descriptive epidemiology study. Methods: AC joint sprains were analyzed from the NCAA Injury Surveillance Program during the 2009-2010 to 2014-2015 academic years. AC joint sprain injury rates, rate ratios, and injury proportion ratios (IPRs) were reported with 95% CIs. Results: In the 25 NCAA sports examined during the 2009-2010 to 2014-2015 academic years, a total of 844 AC joint sprains were reported, for a rate of 1.72 per 10, 000 athlete-exposures (AEs). The majority of AC joint sprains were reported in football (50.4%, n = 425). Most AC joint sprains occurred in competitions (66.0%, n = 557), and the competition rate was 8.58 times the practice rate (95% CI, 7.44-9.89). In sex-comparable sports (ie, soccer, basketball, ice hockey, lacrosse, baseball/softball, indoor track, outdoor track, cross-country, tennis, and swimming and diving), the AC joint sprain rate in men was 4.67 times that of women (95% CI, 3.56-6.14). Most AC joint sprains were caused by player contact (54.7%, n = 462), followed by surface contact (29.0%, n = 245). Of all AC joint sprains, 47.5% resulted in a time loss of <24 hours, and 5.9% were severe. In addition, 9.7% were recurrent, and only 1.0% required surgery. In sex-comparable sports, male athletes had a larger proportion of injuries due to player contact than did female athletes (IPR, 1.50; 95% CI, 1.06-2.13); female athletes had a larger proportion of injuries due to surface contact than male athletes (IPR, 1.55; 95% CI, 1.01-2.38). Also, compared with women, men had a larger proportion of AC joint sprains that were recurrent (IPR, 10.29; 95% CI, 1.45-72.90). Conclusion: The highest rates of AC joint sprains occurred in men's football, ice hockey, and wrestling as well as women's ice hockey. Most AC joint sprains across all sports occurred because of a contact mechanism, particularly from player-player contact. Further research into the specific activities and exposures at the time of injury may lend a better understanding of the causation of these injuries and lead to appropriate interventions to decrease their incidence and severity.